Technology is a solution for MSMEs Sustainability - Lestari, Nurul Sukma; Levyta, Farah; Rosman, Dendy; Zainal, Veithzal Rivai; Affini, Dinar Nur (Universitas Mercu Buana, 2022)
The Corona virus, which began to emerge at the end of 2019 in China, has so far spread widely throughout the world including Indonesia, where this greatly affects various aspects of human life. Many MSME businesses must close because of the current economic situation. Therefore, MSME owners during the COVID-19 pandemic must start rethinking their business strategy. Because only with innovation, micro, small and medium business owners will be able to survive and continue to be sustainable. One of the innovations is to use technology, namely cloud kitchens that are attached to the use of online applications. During the COVID-19 epidemic, this study looks at the possibility of MSME business owners to adopt Cloud-based technology platforms as their new business model. The data for this study were obtained from 100 MSME owners engaged in the food and beverage sector using quantitative techniques. Data processing using SPSS 22.0 program and path analysis. The research findings reveal that there is a relationship between perceived ease of use and perceived benefits that affect the intention to use/adopt cloud kitchens as their new business model. This study contributes to the intention to adopt small businesses towards technology, namely cloud kitchens for MSME owners. Practical implications for other stakeholders are also presented in this study